Application of Soursop Leaf Flour Extract (Annona muricata L.) to Control Armyworms (Spodoptera litura Fab.) on Chili Plants (Capsicum annuum L.) - Hower, Owisen; Fauzana, Hafiz; Deviona, Deviona (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chili peppers (Capsicum annuum L.) are an important agricultural commodity whose productivity often decreases due to infestations by armyworm pests (Spodoptera litura Fab.). Soursop leaf extract (Annona muricata L.) has the potential to become an environmentally friendly botanical pesticide because its active compounds have been proven effective in suppressing feeding activity and causing mortality in these pests. This study aims to determine the effective concentration and the optimal application period of soursop leaf powder extract to control S. litura in chili plants. The study was conducted through two experiments. The first experiment used a completely randomized design with six treatments. The experimental data were analyzed using analysis of variance and further tested with the Honest Significant Difference (HSD) test at a 5% level. The second experiment used treatments with different application periods. The experimental data were statistically analyzed using tabulation and presented descriptively in the form of graphs. The research results showed that the effective concentration of soursop leaf powder extract to control S. litura on chili plants is 100 g/l of water, with an initial mortality time of 4.8 hours after application and a 50% lethal time of 42.0 hours after application, with an LC50 of 3.00% and an LC95 of 26.53%. The best application period for soursop leaf powder extract to control S. litura on chili plants is an application period with spraying every 2 days.